2016
DOI: 10.1371/journal.pone.0149275
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Toll-Like Receptor-Induced CXCL8 Secretion in Human Blood Basophils from Allergic Donors Is Independent of Toll-Like Receptor Expression Levels

Abstract: Human blood basophils have recently gained interest in addition to their function as allergic effector cells. Previous work suggests the involvement of innate immune mechanisms in the development and exacerbation of allergic responses, which might be mediated by basophils. We assayed the expression levels of Toll-like receptor (TLR) 1, 2, 4 and 6 on purified basophils from birch pollen-, house dust mite-, and non-allergic individuals. Additionally, we compared cytokine and chemokine secretion upon TLR stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…We also confirmed that IgE cross-linking induced IL-8 production in equine basophils and IgE-binding monocytes, supporting an FceRI-mediated activation pathway in both cell types. IL-8 production by basophils and IgE-binding monocytes has previously been reported in human studies (57,16,17,19,20) and further supports the use of the well-controlled horse model as a comparative approach for studying IL-8 in the context of IgE-mediated allergy.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We also confirmed that IgE cross-linking induced IL-8 production in equine basophils and IgE-binding monocytes, supporting an FceRI-mediated activation pathway in both cell types. IL-8 production by basophils and IgE-binding monocytes has previously been reported in human studies (57,16,17,19,20) and further supports the use of the well-controlled horse model as a comparative approach for studying IL-8 in the context of IgE-mediated allergy.…”
Section: Discussionsupporting
confidence: 76%
“…To the best of our knowledge, this is the first study to compare IL-8 production between allergic and healthy individuals after IgE stimulation by basophils and IgE-binding monocytes. IL-8 1 basophils have been compared in allergic humans but only after TLR stimulation (16). In this article, we show that allergic individuals have increased percentages of peripheral IL-8 1 IgE-binding monocytes compared with healthy controls upon IgE cross-linking.…”
Section: Discussionmentioning
confidence: 84%
“…We, therefore, recommend inclusion of plots/histograms in the publications to allow the reader evaluating the basophil activation profile. To circumvent bystander effects caused by interaction with other cells basophil purification protocols, as described recently (Steiner et al, 2016 ), may be considered, in particular when investigating more specific questions beyond diagnosis. Overall, the basophil response in BAT is influenced by many so far unpredictable factors which may impair the quality of results in certain cases (Chirumbolo, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous stimulation of the high affinity IgE receptor and TLR4 or TLR9 synergistically upregulated IL-4, CXCL8, IL-13, and CCL5 secretion [124]. Moreover, an elevated CXCL8 secretion was observed in allergic individuals upon TLR1/2 and TLR2/6 stimulation [122]. These findings suggest a connection between the pathogen-induced basophil activation and an allergic response of basophils.…”
Section: The Basophil In the Immune Networkmentioning
confidence: 99%